2022
DOI: 10.5937/ekopolj2203819u
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' intention to buy cheeses with geographical indications: The case of Serbia

Abstract: In recent years, GI cheese consumption has attracted increasing interest among consumers, due to its beneficial properties for local economies and the surrounding environment. Given the high importance that consumers ascribe to geographical indications, considered one of the most relevant attributes for agro-food consumers, this study aims at detecting the main variables that influence purchasing intention for GI cheese. A total of 806 consumers took part in the study from all four regions of the Republic of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Research within the European Community has shown that an increasing number of consumers when buying food opt for products that bear a geographical indication, although such products fetch a higher price than conventional ones. Also, research conducted by Užar et al (2022) showed that consumers who value quality of the products perceive GI as a confirmation of its quality and means of support to local producers. Examples from the EU countries show that a properly established system of GI inevitably brings huge economic benefits -this approach to ensuring the quality and brand of food products ensures the development of the region; it drives the economy, and above all, tourism in a certain region, especially rural areas (Savić, Đurić, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research within the European Community has shown that an increasing number of consumers when buying food opt for products that bear a geographical indication, although such products fetch a higher price than conventional ones. Also, research conducted by Užar et al (2022) showed that consumers who value quality of the products perceive GI as a confirmation of its quality and means of support to local producers. Examples from the EU countries show that a properly established system of GI inevitably brings huge economic benefits -this approach to ensuring the quality and brand of food products ensures the development of the region; it drives the economy, and above all, tourism in a certain region, especially rural areas (Savić, Đurić, 2008).…”
Section: Introductionmentioning
confidence: 99%